Management and use of Nelumbo nucifera Gaertn. in Thai wetlands - Woranuch La-Ongsri (2018)
Management and use of Nelumbo nucifera Gaertn.-the lotus plant-was studied in 58 wetlands distributed throughout Thailand. Although traditionally harvested in extractive systems depending on natural wetlands, N. nucifera is now increasingly being managed. Two hundred eighty informants mentioned 20 different uses, mainly for food, medicine, and religious rites, in both subsistence and cash economies. The uses of N. nucifera appeared to be rather generalized throughout the country even if informants in the northern and central regions knew of more uses and ways of commercializing its products, possibly related to the abundance of wetlands and natural stand in those regions, and maybe also cultural differences. © 2008 Springer Science+Business Media B.V.